New Perspectives on Collective Collaboration Within and Between Change Laboratory Sessions - Camilla Finsterbach Kaup; Susanne Dau (Education Sciences)
This article contributes new knowledge on collaboration within and between Change Laboratory sessions and how it offers the potential to support the zone of proximal development and the expansive learning of participants. The Change Laboratory is a formative intervention method that helps participants transform their practices. This qualitative study examines how six educators participating in a Change Laboratory intervention dealt with problems that arise when implementing digital artifacts in teaching mathematics. We collected data through participant observation between sessions and video recordings during sessions. We conducted the data analysis abductively, using the seven expansive learning actions as an analytical framework. The findings highlight how collaboration between the researcher and the participants, both during and between Change Laboratory sessions, helped support the participants’ zone of proximal development and expansive learning. This close collaboration enabled the educators to collectively reflect on and transform their teaching practices, specifically by incorporating digital artifacts into their educational routines. The study provides important insights into how digital artifacts can be successfully implemented in practice using Change Laboratories, emphasizing the importance of supporting educators in their zone of proximal development. Using a theoretical perspective grounded in cultural-historical activity theory, the study contributes to understanding how change occurs in the educational field.